The impact of hospital experience with out-of-hospital cardiac arrest patients on post cardiac arrest care. (January 2017) - Worthington, Heather; Pickett, Will; Morrison, Laurie J.; Scales, Damon C.; Zhan, Chun; Lin, Steve; Dorian, Paul; Dainty, Katie N.; Ferguson, Niall D.; Brooks, Steven C.; ,
Abstract: Objective: Patient volume as a surrogate for institutional experience has been associated with quality of care indicators for a variety of illnesses. We evaluated the association between hospital experience with comatose out-of-hospital cardiac arrest (OHCA) patients and important care processes. Methods: This was a population-based, retrospective cohort study using data from 37 hospitals in Southern Ontario from 2007 to 2013. We included adults with atraumatic OHCA who were comatose on emergency department arrival and survived at least 6 h. We excluded patients with a Do-Not-Resuscitate order or severe bleeding within 6 h of hospital arrival. Multi-level logistic regression models estimated the association between average annual hospital volume of OHCA patients and outcomes. The primary outcome was successful targeted temperature management (TTM) and secondary outcomes included TTM initiation, premature withdrawal of life-sustaining therapy, and survival with good neurologic function. Results: Our analysis included 2723 patients. For every increase of 10 in the average annual volume of eligible patients, the adjusted odds increased by 30% for successful TTM (OR 1.29, 95% CI 1.03–1.62) and by 38% for initiating TTM (OR 1.38, 95% CI 1.11–1.72). No significant association between patient volume and other secondary outcomes was observed. Conclusions: Patients arriving at hospitals with more experience treating comatose post cardiac arrest patients are more likely to have TTM initiated and to successfully reach target temperature. Our findings have implications for regional systems of care and knowledge translation efforts aiming to improve quality of care for this patient population.